Alcohol and road traffic injuries in Latin America and the Caribbean: a case-crossover study - Borges, Guilherme (Alcohol Clin Exp Res, 2017)
BACKGROUND: This study reports dose-response estimates for the odds ratio (OR) and population attributable risk of acute alcohol use and road traffic injury (RTI). METHODS: Data were analyzed on 1,119 RTI patients arriving at 16 emergency departments (EDs) in Argentina, Brazil, Costa Rica, Dominican Republic, Guatemala, Guyana, Mexico, Nicaragua, Panama and Trinidad & Tobago. Case-crossover analysis, pair-matching the number of standard drinks consumed within the six hours prior to the RTI with two control periods (prior day/week) was performed using fractional polynomial analysis for dose-response. RESULTS: About 1 in 6 RTI patients in EDs were positive for self-reported alcohol 6 hours prior to the injury (country range 8.6%-24.1%). The likelihood of a RTI with any drinking prior (compared to not drinking) was 5 times higher (country range OR 2.50-15.00) and the more a person drinks the higher the risk. Every drink (12.8 g alcohol) increased the risk of an RTI by 13%, even one-two drinks were associated with a sizable increase in risk of an RTI and a dose-response was found. Differences in ORs for drivers (OR=3.51; 95%CI=2.25-5.45), passengers (OR=8.12; 95%CI=4.22-15.61) and pedestrians (OR=6.30; 95%CI=3.14-12.64) and attributable fractions were noted. Acute use of alcohol was attributable to 14% of all RTIs, varying from 7% for females to 19% for being injured as a passenger. Conclusions: The finding that the presence of alcohol increases risk among drivers and non-drivers alike may further help to drive interventions targeting passengers and pedestrians. Routine screening and brief interventions in all health services could also have a beneficial impact in decreasing rates of RTIs. Higher priority should be given to alcohol as a risk factor for RTIs, particularly in Latin America and the Caribbean.